Morphological characteristics of seed starch granules of Fagaceae in South China and their implication in paleodiet - Yu, Tong; Yang, Qing; Deng, Min; Cheng, Nan; Yao, Kaiping; Yang, Wanshu; Ji, Xueping; Zheng, Hongbo (Frontiers in Plant Science, 2022)
Nut fruits likely played a significant role before and during the origin of agriculture; however, relatively little research conducted on morphological characteristics and statistical comparisons of nut fruit starch granule hinder the progress of palaeodietary analysis of prehistorical society. For better species identification of starch granule remaining on tools discovered at archaeological sites, it is desirable to develop a more abundant morphology database of modern nut fruit starch granule as well as the establishment of relevant identification standards. Therefore, nuts from 40 species and 4 genera (Quercus, Lithocarpus, Castanea and Castanopsis) of Fagaceae were collected from South China for statistical measurement and comparative analysis. Starch granule are highly accumulated in 34 species except for 6 species, whose shapes involve oval, subcircular, drop-shaped, rounded triangle, polygonal, spherical caps and bell-shaped types, or a combination of several types, and the average length is between 10-20 μm. According to the research of Quercus phylogeny relationships, it was found that the species in the same section produce similar morphological characteristics of starch granules. This expansion of modern starch presentation and comparison of nuts not only helps to improve the accuracy of the identification of ancient starch and deepen the understanding of plant utilization of ancient humans but also provides a new approach to study Quercus phylogeny.